Improved Outcome of Intestinal Failure in Preterm Infants. Issue 2 (August 2020) - Fredriksson, Fanny; Nyström, Niklas; Waldenvik, Kajsa; Ördén, Helene; Lindblom, Maja; Paulsson, Mattias; Finkel, Yigael; Lilja, Helene Engstrand
ABSTRACT: Objective: The aim of the study was to evaluate the outcome and to identify predictors for survival and enteral autonomy in neonatal intestinal failure (IF). Methods: A retrospective observational study in a Swedish tertiary centre of children born between 1995 and 2016 with neonatal IF, defined as dependency on parenteral nutrition (PN) ≥60 days, starting with PN before the age of 44 gestational weeks. Data were extracted from medical records and predictors for survival and enteral autonomy were identified by the Cox regression model. Time to death and weaning off PN analysis were performed with Kaplan-Meier curves including log rank test. Results: In total, 105 children were included. Median gestational age was 28 weeks (22–42), 50% were born extremely preterm (<28 gestational weeks). PN started at a median age of 2 days (0–147) with a median duration of 196 days (60–3091). Necrotizing enterocolitis was the dominating cause of IF (61%). Overall survival was 88%, 5 children died of sepsis and 4 of intestinal failure-associated liver disease. Survival increased from 75% during 1995 to 2008 to 96% during 2009 to 2016 ( P = 0.0040). Age-adjusted small bowel length of >50% and birth 2009 to 2016 were predictors for survival. Enteral autonomy was achieved in 87%, with positive prediction by small bowel length of >25% of expected for gestational age and remaining ileocecal valve. Conclusions: Preterm neonates with IF, at high risk of IF-associated morbidity, showed a high overall survival rate. Small-bowel length and being born 2009 to 2016 were predictors for survival and remaining ICV and small-bowel length were predictors for enteral autonomy. Abstract : Supplemental Digital Content is available in the text